How to adapt sexual and reproductive health services to the needs and circumstances of trans people- a qualitative study in Colombia - Mariana Calderón-Jaramillo; Ángel Mendoza; Natalia Acevedo; Luz Janeth Forero-Martínez; Sandra Marcela Sánchez; Juan Carlos Rivillas-García (BMC, 2020)
Abstract Background People living a trans-life require access to equitable healthcare services, policies and research that address their needs. However, trans people have experienced different forms of violence, discrimination, stigma, and unfair access barriers when dealing with healthcare providers. Therefore, adapting sexual and reproductive health services with the purpose of providing more equitable, inclusive and discrimination-free healthcare services is an urgent need. The article presents an example of how operative research can be used in order to adjust sexual and reproductive healthcare services to trans people's needs, identities and circumstances. Methods This is a qualitative study written from a constructivist perspective, and it is based on the voices and experiences of trans people in four major cities in Colombia. The research used a combination of focus groups of discussion (n = 6) and in-depth interviews with trans people (n = 13) in Barranquilla, Bogota, Cali and Medellin. This research had two specific objectives: i) identifying the main sexual and reproductive health needs of people living a trans-life; and ii) generating new evidence in order to guide the adaptation of sexual and reproductive health services centered to trans people's needs, identities, and circumstances. Qualitative data codification and analysis was using NVivo. Results Once access barriers to sexual and reproductive health services, unmet sexual and reproductive health needs were identified, the research helped define strategies to adapt sexual and reproductive health services to the needs, identities, and circumstances of people living a trans-life in Colombia. Amongst the main barriers found were healthcare costs, lack of insurance, stigmatization, discrimination and abuse by health care providers. Perhaps among the most notable sexual and reproductive health needs presented were trans-specific services such as sensitive assistance for the transition process, endocrinology appointments, and sex reaffirmation surgeries. Conclusions The evidence obtained from this research allowed Profamilia, a Colombian healthcare provider, to adapt the sexual and reproductive health services it provides to people living a trans-life in Colombia. Furthermore, it was possible for Profamilia to design and implement an inclusive sexual and reproductive health program that specifically addresses trans people's needs, identities, and circumstances.